Development Of Multimedia Ict-Based Online Learning (Cai, Cbi, Mobile Learning And E-Learning) In The Age Of Industrial Revolution 4.0 And Society 5.0 - Anam, Nurul (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
The purpose of this study is to describe the development of online learning based on Multimedia ICT in the Industrial Revolution Age 4.0 and Society 5.0. This research method uses a qualitative method with the type of library research. The results of the study indicate that as part of the effort to reform learning is to take advantage of ICT in learning activities. One of the ICT products that can be used in learning is a computer or laptop/netbook, an Android cellphone and the Internet. By applying ICT-based learning, students can learn